(untitled) (Intent Research Scientific Journal, 2023)
The article analyzes the importace of organizing socio-psychological trainings in educational activities, its goals and objectives, the psychological importance of being able to correctly understand and analyze life contradictions through trainings, generate the skills necessary for the maturation of an individual, and generate the skills to be able to make the right decisions in unforeseen situations.